Pemanfaatan Gula Aren dan Gula Kelapa dalam Pembuatan Kecap Manis Air Kelapa - Usman Pato; Shanti Fitriani (Universitas Riau, 2009)
Utilization of arenga palm sugar in combination with coconut sugar in sweet soy sauce had been studied in this research. The purpose of this research was to find the best combination of arenga palm sugar and coconut sugar to make coconut water ketchup (sweet soy sauce). It was held in crop processing and Analysis Laboratory at Agricultural Faculty, Food Chemistry Laboratory at Fishery Faculty, and Organic Chemistry Laboratory at Engineering Faculty of Riau University. The research was done experimentally by using completely randomized design (CRD) with 5 treatment and 3 replication. The treatments were: KKA0 (0% arenga palm sugar, 100% coconut sugar), KKA1 (25% arenga palm sugar, 75% cocnut sugar), KKA2 (50% arenga palm sugar, 50% cocnut sugar), KKA3 (75% arenga palm sugar, 25% cocnut sugar), KKA4 (100% arenga palm sugar, 0% cocnut sugar), Chemical analysis obtained were the protein content, total dissolved solid, sucrose concentration, and viscosity. The utilization of arenga palm sugar and coconut sugar in making coconut water ketchup influenced the protein content, sucrose concentration, but it did not influence the total dissolved solid and viscosity. The KKA3 (75% palm sugar, 25% coconut sugar ) is the best combination to make coconut water ketchup because it met SNI 001-3543-1994, with protein content of 3,61% and total dissolved solid of 50,53%.